Dental Trauma in the Northern Region of the State of Ceará: An Observational Study - , Mateus Jorge Moreira, Yann Nobre Viana, Gean Erick da Rocha de Maria, Clara de Assis Araujo de Oliveira, Lucas de Castro Silva Ribeiro, Francisco Samuel Rodrigues Carvalho, Adriana Kelly de Sousa Santiago Barbosa (Archives of Current Research International, 2024)
Introduction: Oral and dental trauma (ODT) results from sudden forces acting on the teeth and/or adjacent tissues. The etiology is complex and often multifactorial, along with cultural and social aspects that can favor the occurrence of these traumas. Epidemiological studies on dental injuries help to plan education and prevention actions. Aim: The aim of this study was to determine the epidemiological pattern of patients affected by ODT over a 7-year period, treated at the Center for the Study of Patients Victims of Oral and Dental Trauma in Sobral, a project of the Federal University of Ceará. Methodology: A descriptive, epidemiological and cross-sectional study was carried out by analyzing the medical records of all patients treated between 2016 and 2023. The data collected included gender, age, date and place of injury, diagnosis, teeth affected and time since trauma. Results: The study included 99 patients with 169 affected teeth. Males were predominantly affected (73.3%), with the upper right central incisor being the most frequently injured tooth (21.9%). In addition, 18.18% of patients had a history of previous injuries. The most affected age group was children aged 0-12 (60.6%), with falls from a height being the main cause (29.29%), followed by bicycle accidents (12.12%). Most injuries occurred at home (35.35%). Clinical Significance: ODTs represent an important public health problem. This study corroborates the existing literature, highlighting that dental trauma predominantly affects young males and impacts the anterior maxillary region. Understanding the risk factors is crucial for developing effective preventive and educational strategies, ensuring timely and appropriate emergency care.